The Souk Al-Manakh: The anatomy of a pure price-chasing bubble - Frank Veneroso; Mark Pasquali (Levy Economics Institute of Bard College, 2021)
It is widely agreed that the Nasdaq during the dot-com era 20 years ago was a full-fledged stock market bubble. Recently, the US stock market according to many metrics has become significantly more speculative and overvalued than it was at the dot-com peak 20 years ago. In both instances, a very broad subset of stocks became so highly valued that speculation in them had to be untethered from all fundamentals: the essence of what we call a "pure price-chasing bubble." This paper, drawn from a book in progress, examines the history of stock markets for comparable pure price-chasing bubbles, finding nine or so which have ever reached such a speculative extreme, with an over-the-counter market in Kuwait in the early 1980s called the "Souk al-Manakh" representing the most extreme example. Based on my personal exposure to this Souk al-Manakh almost 40 years ago, I describe this anatomy and thereby make transparent the recurrent dynamics - on the way up and on the way down - of these greatest asset bubbles in human history. When one applies this framework to the current US stock market, one sees that the stock market in the US today will likely follow the disastrous path of the dot-com market.
Keywords: D84; E12; E5; E71; G1; 330; Asset Bubble; Stock Market; Over-the-Counter Markets; Price-Chasing Bubble; Conventions